2013
DOI: 10.1007/s10164-013-0390-0
|View full text |Cite
|
Sign up to set email alerts
|

Winter space use of coyotes in high-elevation environments: behavioral adaptations to deep-snow landscapes

Abstract: In the last century, coyotes (Canis latrans) have expanded their range geographically, but have also expanded their use of habitats within currently occupied regions. Because coyotes are not morphologically adapted for travel in deep snow, we studied coyote space use patterns in a deep-snow landscape to examine behavioral adaptations enabling them to use high elevations during winter. We examined the influence of snow depth, snow penetrability, canopy cover, and habitat type, as well as the rates of prey and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
(56 reference statements)
3
14
0
Order By: Relevance
“…On the VCNP, we found the territories of the resident coyote packs to be relatively stable both seasonally and annually, similar to other studies in high-elevation environments (Gese et al 1996a;Dowd et al 2014). Even when availability of various sized prey changed seasonally and annually (Gifford 2013), space use and social ecology of the coyote packs remained unchanged.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the VCNP, we found the territories of the resident coyote packs to be relatively stable both seasonally and annually, similar to other studies in high-elevation environments (Gese et al 1996a;Dowd et al 2014). Even when availability of various sized prey changed seasonally and annually (Gifford 2013), space use and social ecology of the coyote packs remained unchanged.…”
Section: Discussionsupporting
confidence: 87%
“…There have been numerous studies of coyote (Canis latrans) social and spatial ecology throughout North America (e.g., Messier and Barrette 1982;Andelt 1985;Mills and Knowlton 1991), but few studies have been conducted on coyotes at high elevations (e.g., Bekoff and Wells 1980;Bowen 1982;Gese et al 1996a;Dowd et al 2014). A general consensus of studies indicates coyote space use can be stable through time (Kitchen et al 2000a;Young et al 2006), but varies by geographic location.…”
Section: Introductionmentioning
confidence: 99%
“…We expected that both snowpack characteristics would increase reliance on compacted roads and trails, yet there was a negative association with penetrability. The movement of both species is compromised by deep powdery snow (Halpin and Bissonette , Crête and Larivière , Gese et al , Dowd et al ), which limits locomotion (Murray and Boutin , Crête and Larivière ) and increases reliance on compacted snow surfaces or habitats that ameliorate deep snowpack when snow depth increases (Halpin and Bissonette , Gese et al , Dowd et al ), as observed in this study. However, extreme cold and deep, powdery snow can limit coyote and red fox movements (Bekoff and Wells , Halpin and Bissonette , Meia and Weber ), and these conditions were common during mid‐winter surveys and at higher elevations (Sirén ).…”
Section: Discussionsupporting
confidence: 66%
“…Mammalian carnivores greatly influence lower trophic levels (Crooks and Soulé , Sergio et al ) yet respond differentially to climate and environment (Pozzanghera et al ), and habitat loss and fragmentation (Crooks ). Those living in northern latitudes are sensitive to changes in snowpack and include habitat specialists and generalists (Dowd et al , Pozzanghera et al ). For example, Canada lynx ( Lynx canadensis ) are adapted for deep snow and primarily inhabit boreal forest (Murray et al , Hoving et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation